2014
DOI: 10.48550/arxiv.1411.3316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lowest Landau Level Stress Tensor and Structure Factor of Trial Quantum Hall Wave Functions

Abstract: We show that for a class of model Hamiltonians for which certain trial quantum Hall wavefunctions are exact ground states, there is a single spectral density function which controls all two-point correlation functions of density, current and stress tensor components. From this we show that the static structure factors of these wavefunctions behaves at long wavelengths as s4k 4 where the coefficient s4 is directly related to the shift: s4 = (S − 1)/8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…We thank D. T. Son for sharing with us Ref. [60], which gives an alternative derivation of (70). The work was supported by NSF DMS-1206648, DMS-1156656, DMR-MRSEC 0820054, John Templeton Foundation and PVE grant from the CNPq-Brazil Science Without Boarders Program.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We thank D. T. Son for sharing with us Ref. [60], which gives an alternative derivation of (70). The work was supported by NSF DMS-1206648, DMS-1156656, DMR-MRSEC 0820054, John Templeton Foundation and PVE grant from the CNPq-Brazil Science Without Boarders Program.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The same conservation law was derived previously in Ref. [40] using a LLL field theory formalism. The connection of volume-preserving diffeomorphism and quantum Hall physics was also noticed in Refs.…”
Section: Connection To Quantum Hall Effectmentioning
confidence: 72%
“…In Ref. [24] it was proven that I + (ω) = 0 for the trial ground states of model Hamiltonians with contact interactions. While there is no argument that I + should be zero for more general Hamiltonians, numerically it was found that for Coulomb interaction I + is much smaller than I − for the Laughlin ν = 1/3 state [20].…”
Section: Regimementioning
confidence: 99%
“…First we write down formulas for the full stress tensor. For the model Hamiltonian, at the long wave length regime k ∼ 0, the full stress tensor is the same as T kin [24]. For the general case, one needs to take into account the potential-energy term in the Lagrangian.…”
Section: Appendix A: Detailed Derivation Of Raman Scattering Couplingmentioning
confidence: 99%